Characteristics of hand injuries caused by corn-husker equipment: a new type of agricultural injury - Pang, Chao-Jian; Huo, Xiao-Yan; Liu, Yuan; Yang, Zong-You; Liu, Lu; Fan, Xiao-Bo; Xu, Shang-Wen (Frontiers in Surgery, 2025)
ObjectivesThis study aims to describe the nature and incidence of hand injuries caused by corn-husker machines, as well as the accident conditions and treatment experiences.MethodsThis retrospective investigation included 34 patients treated at a single institution from August 2018 to August 2021 with postoperative follow-up of more than 12 months. The Hand Injury Severity Scoring System (HISS) was applied to identify the degree of hand injury. Depending on the type of damage, different surgical methods were used, including debridement and suturing, amputation, fracture fixation, negative pressure wound therapy (NPWT), skin flap and skin graft procedures, replantation, and tendon repair. Bacterial culture and antibiotic sensitivity tests were performed when wound secretions were present.ResultsThe average age was 42.1 years, and 76.4% of the patients were male. 17.6% were classified as HISS I, 20.6% each as HISS II and HISS III, and 41.2% as HISS IV. Among the 83 injured fingers (6 thumbs, 13 index, 12 middle, 10 ring, and 7 little fingers), the finger amputation rate was 57.8%. The most common complication was infection, with 13 cases of postoperative infection, resulting in an infection rate of 38.2%. Although NPWT played an important role in treatment, there was no significant difference in infection rates between wounds treated with NPWT and those treated without. Median hospitalization duration was 35 days (IQR: 27–45); median treatment cost was $4740 (IQR: $3255–$6215). Infections significantly impacted both hospitalization duration and treatment costs.ConclusionCorn-husker machine-related hand injuries represent a new type of hand trauma and are often severely mutilating. The selection of appropriate surgical methods and the prevention of infection are crucial aspects in treating such injuries.